Decacene: On‐Surface Generation. Issue 39 (17th August 2017) - Krüger, Justus; García, Fátima; Eisenhut, Frank; Skidin, Dmitry; Alonso, José M.; Guitián, Enrique; Pérez, Dolores; Cuniberti, Gianaurelio; Moresco, Francesca; Peña, Diego
Abstract: Acenes are intriguing molecules with unique electronic properties. The difficulties in their preparation owing to low stability under ambient conditions are apparent because successful syntheses of long unsubstituted acenes are still scarce, in spite of the great attention they have attracted. Only unsubstituted acenes up to heptacene have been isolated in bulk, with nonacene being the largest acene detected to date. Herein we use on‐surface assisted reduction of tetraepoxy decacene precursors on Au(111) as the key step to generate unprecedented decacene which is visualized and its electronic resonances studied by scanning tunneling microscopy (STM) and spectroscopy (STS). Abstract : Decathletes : Combined efforts of organic synthesis and on‐surface chemistry have led to the preparation of decacene for the first time. An iterative sequence of aryne cycloadditions was used to synthesize stable tetraepoxy precursors which were reduced on Au(111) to obtain unprecedented decacene as visualized by scanning tunneling microscopy (STM).